2022
DOI: 10.1136/heartjnl-2022-321208
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 international experience in paediatric patients with congenital heart disease

Abstract: ObjectiveAs COVID-19 continues to affect the global population, it is crucial to study the impact of the disease in vulnerable populations. This study of a diverse, international cohort aims to provide timely, experiential data on the course of disease in paediatric patients with congenital heart disease (CHD).MethodsData were collected by capitalising on two pre-existing CHD registries, the International Quality Improvement Collaborative for Congenital Heart Disease:Improving Care in Low- and Middle-Income Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For instance, there is evidence to suggest that diabetic children who maintain good glycemic control are at no greater risk than the general population [40, 78, 155, 156]. Similarly, children with congenital heart disease who have undergone surgical repair or no longer have a hemodynamically significant abnormality may be at lower risk [35, 157].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there is evidence to suggest that diabetic children who maintain good glycemic control are at no greater risk than the general population [40, 78, 155, 156]. Similarly, children with congenital heart disease who have undergone surgical repair or no longer have a hemodynamically significant abnormality may be at lower risk [35, 157].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] However, many studies suggested a higher risk of morbidity among children with COVID-19 admitted to hospitals. [ 14 15 ] A large analysis of 339 cardiac patients from 35 international centers, who had a recent COVID illness[ 16 ] reported a 25% hospitalization rate and 15% of children required ICU care. The study reported an overall mortality of 5%, mostly from the non-US centers.…”
Section: Outcomes Of Children With Heart Disease and Covid-19mentioning
confidence: 99%
“…The study reported an overall mortality of 5%, mostly from the non-US centers. [ 16 ] A large retrospective study from India,[ 12 ] which included 94 hospitalized patients, however, reported a high mortality rate (13.8%). The study is one of the largest and represents real-time, cross-sectional practice across India.…”
Section: Outcomes Of Children With Heart Disease and Covid-19mentioning
confidence: 99%
“…The condition was fi rst described in May 2020 in UK, with evidence of a hyperinfl ammatory condition similar to Kawasaki disease [9]. These children presented with respiratory failure, cardiovascular insuffi ciency, or liver involvement [10][11][12]. The condition was termed multisystem infl ammatory syndrome in children (MIS-C) and adolescents temporarily related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%